A 5 GHz linear laser diode driver for ROF transmission systems. Issue 1 (18th November 2014) - Chen, Yingmei; Zheng, Yilin; Zhang, Li
ABSTRACT The design of a 42 mA laser diode (LD) driver for 5 GHz radio‐over‐fiber transmission systems is presented in this article. The proposed linear LD driver adopted a single‐ended two‐stage amplifier structure with the operating voltages of 1.8 and 3.3 V, respectively. The technique of self‐biased cascade amplifier is used to increase the gain and alleviate the danger of gate oxide breakdown. The measurement results show that the linear amplifier achieves the power gain of 15.3 dB and the output 1 dB compression point of 16.4 dBm at 5.58 GHz. The corresponding output modulation current is up to 42 mA at the 1 dB compression point. The total chip area is only 710 × 580 μm2 with the all on chip input and output matching network, and the power consumption is 128 mW. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:41–45, 2015